Isolation and Characterization of Flavonoids from The Leaves of Local Orthosiphon Stamineus - Hossain, M. Amzad, Amzad; Z (Zhari Ismail), Ismail (Malaysian Journal of Science, 2005)
Six flavonoid compounds were isolated from the leaves of local medicinal plant Orthosiphon stamineus. On the basis of chemical and spectral analyses their structures were elucidated as equpatorin 1 , sinensetin 2, 5-hydroxy-6, 7, 3’, 4’-tetramethoxyflavone 3, salvigenin 4, 6-hydroxy-5, 7, 3’-trimethoxyflavone 5 and 5, 6, 7, 3’-tetramethoxy-4’-hydroxy-8-C-prenylflavone 6. Latter compound was isolated from this plant for the first time. Identification of known compounds were established through comparison of spectral data (UV, IR, MS and NMR) with literature values.